Erratum: to the paper “Influence of elastic deformation on the residual ellipticity of polished optical materials” - Maslov, V.P.; Sarsembaeva, A.Z.; Sizov, F.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The elastic deformation of thin mirrors is widely used in systems of adaptive optics, however, of influence of elastic deformations on parameters of reflected polarised light in the literature. Using the method of ellipsometry, the influence of elastic deformation on the residual ellipticity of polished samples made of optical materials was studied. The results obtained during the researches have shown that the appli- cation of elastic deformations leads to essential changes of the minimum ellipticity tgρ of polished samples, which testifies to the necessity to take into account this circumstance for devices of adaptive optics, input windows, cryostats and other optical parts working with the changing temperature.